1980
DOI: 10.1103/physrevc.21.620
|View full text |Cite
|
Sign up to set email alerts
|

Q-value dependence of inelastic scattering and multinucleon transfer reactionsAl27+et al.

Abstract: Despite the low bombarding energy, the general features of (i) energy spectra, (ii) the optimum Q values Q,~, and (iii) angular distributions in 5 MeV intervals in Q are very similar to those of much higher energy data of heavier systems: i.e. , (i) dominance of deep inelastic reactions, (ii) Q,ff values well reproduced by the "universal" relations previously found for deep inelastic reactions, and (iii) cr(8,Q) of a form A expf -p,(Q)8]/sin8. The variations of Q, "with 8, and of p, with Q and n, the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
8
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
4
8
0
Order By: Relevance
“…5 for comparison. It is seen that, in all reactions, the time scale decreases as the fragment charge increases, which is in conformity with a previous study by Mikumo et al [54]. This is expected because the heavier fragments (nearer to the projectile) require less nucleon exchange and therefore less time; on the other hand, the Si reactions, which is actually the case (Fig.…”
Section: Angular Distributionsupporting
confidence: 91%
“…5 for comparison. It is seen that, in all reactions, the time scale decreases as the fragment charge increases, which is in conformity with a previous study by Mikumo et al [54]. This is expected because the heavier fragments (nearer to the projectile) require less nucleon exchange and therefore less time; on the other hand, the Si reactions, which is actually the case (Fig.…”
Section: Angular Distributionsupporting
confidence: 91%
“…al. [8] for the same reaction at 88 MeV, the time scales decrease as the fragment charges increase. This is expected because the heavier fragments ( nearer to the projectile ) require less number of nuleon transfer and therefore less time; on the other hand the emission of lighter fragments requires exchange of more number of nucleons and therefore longer times.…”
mentioning
confidence: 99%
“…Several studies made earlier for 16 O + 27 Al system at incident energies in the range of ∼60 -100 MeV have indicated that fragments emitted in the reaction are mainly originating from cluster transfer [16], projectile sequential breakup [2] and multi-nucleon transfer [7][8][9] processes. The role of direct two-body and three-body projectile breakup in fragment emission from 16 O + 27 Al reaction in the energy range of ∼70 -125 MeV have also been investigated recently [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations